Magnetic anisotropy and organization of nanoparticles in heads and antennae of neotropical leaf-cutter ants, Atta colombica (2014)
Oriented magnetic nanoparticles have been suggested as a good candidate for a magnetic sensor in ants. Behavioural evidence for a magnetic compass in neotropical leaf-cutter ants, Atta colombica (Formicidae: Attini), motivated a study of the arrangement of magnetic particles in the ants' four major body parts by measuring the angular dependence of the ferromagnetic resonance spectra at room temperature. Spectra of the thoraces and those of the abdomens showed no significant angular dependence, while those of the antennae and those of the heads exhibited a periodic dependence relative to the magnetic field. Fitting of the angular dependence of the resonant field resulted in an unexpected magnetic anisotropy with uniaxial symmetry. High values of the first order anisotropy constant were observed for the magnetic material in antennae (?2.9? × ?105?erg?cm?3) and heads (?1? × ?106?erg?cm?3) as compared to body parts of other social insects. In addition, the magnitude of the anisotropy in the heads was comparable to that observed in magnetite nanoparticles of 4–5?nm diameter. For the antennae, the mean angle of the particles' easy magnetization axis (EA) was estimated to be 41° relative to the straightened antenna's long axis. For the heads, EA was approximately 60° relative to the head's axis running from midway between the spines to the clypeus. These physical characteristics indicate organized magnetic nanoparticles with a potential for directional sensitivity, which is an important feature of magnetic compasses.